2021
DOI: 10.4028/www.scientific.net/jbbbe.50.59
|View full text |Cite
|
Sign up to set email alerts
|

WeMos IoT Controller-Based Low-Cost Fall Detection System for Elderly Users

Abstract: Fall detection systems for the elderly are very important to protect this type of users. The early detection of the fall of the elderly has a major impact on saving their lives and avoiding the deterioration of the negative medical effects resulting from the effect of the patient falling on a hard surface. One of the constraints in fall detection systems are false-negative errors (no fall detection) or false-positive errors (sending a false warning without real fall accident). These errors have to be reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The main goal of the proposed work is to evaluate, which parameter should be used in future design for hazardous gases detection and alarming systems. A combination of two different gas measurement parameters such as the IAQ-index and TVOC will allow the system to minimize false-positive as well as false-negative gas detection errors [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of the proposed work is to evaluate, which parameter should be used in future design for hazardous gases detection and alarming systems. A combination of two different gas measurement parameters such as the IAQ-index and TVOC will allow the system to minimize false-positive as well as false-negative gas detection errors [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The systems in [27,29,30,40,49,50] are good examples for IoT-based implementation which is one of the important improvements in the ongoing and next generation of hazardous gases detection and alarming systems design [71,72]. As the presented review focus on the mobile systems, we found that the IoT-based systems can achieve the following advantages over implementations: Several systems in this review use ZigBee communication modules to establish the wireless communication between the sensors node and the monitoring station, which is a good choice for indoor short-range data transferring in WSN.…”
Section: Communication Technologymentioning
confidence: 99%
“…Every year, one in three elderly people fall, which can cause serious injuries, hospital stays, and even death [1], impairing their functionality and reducing their mobility, independence, and quality of life [2]. To lessen false-negative and false-positive mistakes, fall detection systems' accuracy must be increased [3]. Several fall detection and emergency warning systems have been created to solve this issue, and they automatically notify the necessary care groups when a fall is detected [4] [5].…”
Section: Introductionmentioning
confidence: 99%